Ketika Nasionalisme Membusuk - Jajang Jahroni (Studia Islamika, 2005)
Book Review: Jacques Bertrand, Nationalism and Ethnic Conflict in Indonesia, Cambridge: Cambridge University Press, 2004, 278 + xxiii pp.When the New Order replaced the Old Order in the 1960s, a number of social, economic, political, and religious issues required the immediate attention of the new ruling regime. However, instead of dealing with these issues in a manner suitable of their severity, the New Order regime merely tried to simplify the complexities of the problems by promoting national unity through the introduction of its own concept of nationalism.DOI: 10.15408/sdi.v12i3.586